Innovation in Literacy Management in Indonesian Language Learning: Efforts to Foster a Love for Writing Creative Stories - Della Fefi Yunitasari; Choirun Nisa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Creative writing skills are very important in Indonesian language learning, but many elementary school students still have difficulty generating ideas and writing coherently. This study aims to analyze literacy management innovations using YouTube animated videos through the POAC (Planning, Organizing, Implementing, Controlling) framework as an effort to increase students' interest and ability in creative writing at SDN 5 Ketro. The research was conducted at SDN 5 Ketro, Indonesian. Methodology: Using a descriptive qualitative approach with a case study design, data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model.Results: The results show that the use of animated videos effectively stimulates students' imagination, increases engagement, and strengthens the coherence and creativity of their writing. The POAC based management structure also supports smoother implementation, although challenges such as limited facilities, varying student abilities, and limited literacy time remain obstacles.Applications/Originality/Value: Overall, this innovation demonstrates that digital media can strengthen literacy learning when integrated with consistent and well-organized management. The findings imply that schools need to improve technological readiness, teachers should develop structured literacy plans, and literacy programs must shift toward adaptive digital-based management to meet the needs of 21st-century learning.